Potencial antioxidante de los extractos obtenidos del pericarpio y la semilla del fruto de Garcinia mangostana L. Según el método de extracción (2023)
Scientific studies have shown that the methods of extraction of solutions derived from plant raw materials may adversely affect plant´s antioxidant capacity. Moreover, the study of the potential use of plant residues (exocarp and seed) ensures the generation of added value to productive chains and thus, a significant reduction in emissions of these to landfills. This research evaluated the antioxidant capacity of epicarp and seeds of Garcinia mangostana L. fruit with the use of three extraction methods (Soxhlet, hydrodistillation and steam stripping) using absolute ethanol as a solvent and water. As standards of comparison, samples of commercial soybean oil and Butylated hydroxytoluene (BHT), a synthetic origin antioxidant, were employed. In the pericarp of G. mangostana L. fruit, the Soxhlet extraction and steam stripping showed significant values at different concentrations, denoting an antioxidant effect on soybean oil by reduction of the peroxide. For the seed, the vapor stripping method yielded higher values in the antioxidant activity along to the most concentrated solutions. © 2016, Universidad Nacional de Colombial. All rights reserved.